2011
DOI: 10.1111/j.1743-6109.2011.02363.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Infection Dip Suggestions for the Coloplast Titan Inflatable Penile Prosthesis in the Era of the Infection Retardant Coated Implant

Abstract: Introduction Infection is the worst complication seen with inflatable penile prosthesis (IPP). Both the American Medical Systems (AMS) and Coloplast IPP have infection retardant coatings. AMS is coated at the factory with rifampicin and minocycline (InhibiZone). The Coloplast IPP has a hydrophilic coating covalently bonded to its components that will absorb any aqueous solution before implantation and provides increased surface lubricity to decrease bacterial adherence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…In a study by Wilson et al. the zones of inhibition against these specific bacteria using the hydrophilic‐coated Coloplast implant immersed in several antibiotic solutions and InhibiZone‐coated IPP strips demonstrated the Coloplast IPP strips (except the ones soaked in bacitracin) had greater zone of inhibition compared with InhibiZone‐impregnated IPPs [20]. The authors also suggested that trimethoprim sulfamethoxazole solution is to be the optimum solution to soak the hydrophilic‐coated IPPs.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Wilson et al. the zones of inhibition against these specific bacteria using the hydrophilic‐coated Coloplast implant immersed in several antibiotic solutions and InhibiZone‐coated IPP strips demonstrated the Coloplast IPP strips (except the ones soaked in bacitracin) had greater zone of inhibition compared with InhibiZone‐impregnated IPPs [20]. The authors also suggested that trimethoprim sulfamethoxazole solution is to be the optimum solution to soak the hydrophilic‐coated IPPs.…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Mentor (now Coloplast) introduced the Titan coating, a hydrophilic substance that reduced bacterial adherence and absorbs and distributes the antibiotic coating that the surgeon chooses to use intraoperatively [10]. Several studies have shown the benefit of these antibiotic‐coated designs [13–15]. This is also likely a significant reason for the low infection rate in our study.…”
Section: Discussionmentioning
confidence: 66%
“…This variation has the advantage of tailoring the antibiotic to the surgeon's discretion and the site's susceptibility profile. In vitro studies have suggested that the hydrophilic coating may have an improved antibacterial effect over rifampin/minocycline coating, 23 yet both coatings seem to be equally effective clinically. A recent report by Serefoglu and colleagues 24 analyzed over 36,000 primary PPs with hydrophilic coating and found that the infection rate of coated devices decreased to 1.4% compared to 4.6% for uncoated models at 11 years follow-up.…”
Section: Salvage Reimplantationmentioning
confidence: 98%